2021
DOI: 10.4103/1735-3327.313121
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of dental care in Iranian pregnant women

Abstract: Background: Although dental care attendance during pregnancy has been recommended by guidelines and institutions, the demand for dental services is still low among pregnant women. The aim of this study was to examine the prevalence of not receipt dental care and also determinants of that during pregnancy. Materials and Methods: This population-based study was conducted on 4071 mothers in 10 provinces of Iran, during 2014–2015. We calculated the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…2 The results of a population-based study during 2014-2015 among 4071 Iranian pregnant women in 10 different provinces showed that about 55% of pregnant women are not visited by a dentist during pregnancy. 7 More than half of Iranian pregnant women brush their teeth once a day, and the average DMFT score of pregnant women was reported as 3.93±5.64. 8 Pregnant women may not have enough knowledge about the effects of their oral health on the fetus and the consequences of their pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…2 The results of a population-based study during 2014-2015 among 4071 Iranian pregnant women in 10 different provinces showed that about 55% of pregnant women are not visited by a dentist during pregnancy. 7 More than half of Iranian pregnant women brush their teeth once a day, and the average DMFT score of pregnant women was reported as 3.93±5.64. 8 Pregnant women may not have enough knowledge about the effects of their oral health on the fetus and the consequences of their pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Extant research on the link between occupational status and oral health is scarce, and most of it is from outside the U.S. The small available literature suggests that most pregnant women receive insufficient dental care, [ 21 23 ] with the main barriers being financial stress (e.g., costs), [ 22 , 24 , 25 ] work-related aspects (e.g., time constraints, discrimination), [ 24 – 26 ] but also a lack of information about pregnant women’s oral health. [ 27 ] Employment status (e.g., related to financial and insurance access) and education (e.g., unawareness of oral hygiene or the effects of pregnancy on oral health) also have a role in the mother’s visit to dental care.…”
Section: Introductionmentioning
confidence: 99%